Interaction and immune regulations of innate lymphoid cells and plasmacytoid dendritic cells in skin inflammatory diseases - Chen, Y-L (2018)
The skin is equipped with an immune network providing surveillance and effector function. Plasmacytoid dendritic cells (pDCs) are found to accumulate in skin wounds, yet the mechanisms of their role in skin wound healing are hitherto unstudied. Here, BDCA-2+ DCs were shown to infiltrate in vivo human wounds, showing heterogeneity based on differential expression of CD123, with a CD123int DC subset expressing CD1a at high levels. The CD1a+-bearing subsets could be derived from blood pDCs and presented self-lipid antigens to CD1a-reactive T cells, inducing interleukin (IL)-22 production. Using single-cell RNA sequencing, human skin wound CD123intBDCA 2+ CD1a+ DCs were shown to acquire features compatible with a role in lymph node homing and antigen presentation. Plasmacytoid DCs and group 3 innate lymphoid cells (ILC3) have emerged as important mediators of skin inflammation, but, the mechanisms of their interaction have remained elusive. Here, it was identified that type I interferons (IFN-I), produced by pDCs, negatively regulated IL-22 producing capability of ILC22, an ILC3 subset, and positively mediated their co-stimulatory marker expression. ILC22 also presented peptide antigens to CD4+ T cells. While exogenous IL 1beta and IL 23 dampened the antigen presenting capacity of ILC22, addition of IFN I rescued their ability, and the study of psoriatic ILC22 revealed a hyper responsiveness to IFN-I. These data demonstrate early infiltration of a previously unrecognised subset of CD123intBDCA-2+CD1a+ DCs in human skin wounds which can present lipid antigens to autoreactive T cells, contributing to the wound healing process. Furthermore, the blood CD123hiBDCA 2+ pDCs produce IFN-I and regulate ILC22 to promote T cell functions. Overall, this study reveals a new route for potential therapeutic manipulations in maintaining skin homeostasis: the pDC-IFN-I-ILC22-T cell axis.